KOMPETENSI PEDAGOGIK DOSEN UNIVERSITAS BUANA PERJUANGAN KARAWANG DENGAN CIPP - Repelita, Tridays; Sholeh Hidayat; Nurul Anriani; Depi Prihamdani; Yogi Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to evaluate the pedagogical competence of lecturers at Buana Perjuangan University, Karawang. This research is qualitative research with emphasis on the CIPP evaluation model. The data in this research was obtained from documents, interviews and research questionnaires. The focus of this research is lecturers' pedagogical competence in managing a safe and comfortable learning environment, effective student-centered learning and assessment, and student-centered feedback. Based on the results of research assessing the capabilities of lecturers at Buana Perjuangan University through the CIPP model evaluation, the results showed that the pedagogical competence of lecturers at Buana Perjuangan University, Karawang, was very good. Keyword: evaluation of lecturers' pedagogical competence, Buana Perjuangan Karawang University, CIPP